Predicting academic achievement and student absences in high school: The roles of student and school attributes - Sideridis, Georgios; Alamri, Abeer A. (Frontiers in Psychology, 2023)
The present study aims at examining predictors of high school students’ academic achievement from student-level and school-level predictors in the Kingdom of Saudi Arabia, especially in light of policy mandates on educational reform in accordance with Vision 2030. Participants were 528,854 individuals who took on the Standard Achievement Admission Test (SAAT), along with other demographic variables. The mean age of participants was 19.7 years with an SD = 1.87. There were 234,813 males and 294,041 females. A Multilevel Random Coefficient Modeling (MRCM) model was engaged to identify predictors of academic achievement. Results indicated the positive roles of being a female, having educational parents, being educated in religious schools or large schools, and having small student-to-teacher ratios and the negative roles of student absences, student age, and being educated in new schools. Results are viewed under the lenses of new policy mandates on educational reform in the Kingdom of Saudi Arabia.